Video encryption scheme using hybrid encryption technology. Issue 1 (6th February 2020) - Han, Qingqing; Wang, Liejun; Lee, Yongming; Qin, Jiwei
In recent years, researchers have proposed a number of encryption algorithms and encryption schemes to protect the privacy of individuals or businesses. However, these encryption algorithms and encryption schemes are difficult to achieve a certain balance in term of encryption efficiency and security. In order to achieve this goal as much as possible, we propose a hybrid encryption technique, which makes the best use of two encryption techniques to achieve higher security and faster speed of encryption algorithm. We introduce two techniques in this hybrid encryption scheme. The first is scrambling and the second is encryption. We evaluated the performance of encrypted video by comparing the PSNR and SSIM values of the scrambled video and the encrypted video. Experimental results show that the proposed scheme has high encryption efficiency and good security.